Penentuan lokasi Pada Perencanaan dan Perancangan Museum Seni Rupa di Gianyar: BAHASA INDONESIA - I Gede Candra Santika; I Ketut Sugihantara; Ida Bagus Gede Parama Putra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The essence of works of art is the footprints of the artist in the cultural history of mankind. All of this can be tracked and appreciated on an ongoing basis if the works of art are properly stored in a representative place, one of which is an art museum. Museum of Fine Arts, Painting and Sculpture is a place or place for someone to express their thoughts, feelings and imagination through the media of paintings or sculptures that have a certain message or just as self-expression shown to a large audience. In general, the location is in accordance with the planning and design of the Museum of Art Rupa is Singakerta Village, Ubud District. Where Singakerta Village is part of the Ubud sub-district which is the art center of the Province of Bali, there are also many artists who are proficient in making works of art such as fine art.